2012
DOI: 10.1002/hlca.201200004
|View full text |Cite
|
Sign up to set email alerts
|

The Reactions of α‐Ylidene (Vinylidene, Benzylidene, Styrylmethylidene) Bis[carbonyls] with Copper Mono/Bis[carbonylcarbenoids]

Abstract: The [Cu(acac) 2 ]-catalyzed reactions of various a,b,g,d-unsaturated bis-ketones/bis-esters/bis-keto esters with dimethyl diazomalonate and ethyl diazoacetate were studied. Total steric/electronic convenience of the present reaction paths was investigated. Methoxy/nitro substituents in m-/p-positions on benzylidene biscarbonyls did not alter the general routes of the reactions, supporting concerted mechanism. Dihydrobenzoxepine/oxepine formation was sterically sensitive to the related pre-ring conformation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The conformations of the α,β-enones have a significant influence on the reaction pathway. For example, the reaction of ( Z )-enones 132 and 134 with dimethyl diazomalonate produced the formal [3+2] adducts, ioxole derivatives 133 and 135 , respectively (Scheme ) . Note that Rh­(II) acetate can also catalyze this type of [4+1] annulation of the electron-rich 1,3-dienes and acetyl-acetone with the diazocompounds .…”
Section: Diazo Reagents-based Formal [4+1] Annulationmentioning
confidence: 99%
“…The conformations of the α,β-enones have a significant influence on the reaction pathway. For example, the reaction of ( Z )-enones 132 and 134 with dimethyl diazomalonate produced the formal [3+2] adducts, ioxole derivatives 133 and 135 , respectively (Scheme ) . Note that Rh­(II) acetate can also catalyze this type of [4+1] annulation of the electron-rich 1,3-dienes and acetyl-acetone with the diazocompounds .…”
Section: Diazo Reagents-based Formal [4+1] Annulationmentioning
confidence: 99%
“…Ylide can be formed in two ways: by the interaction of a vinyl carbonyl compound and a metal carbene (Scheme , a, path A) or by a coupling of a vinyl carbene and a carbonyl group (Scheme , a, path B). The first pathway (A) was investigated in the works of the Anaç and the Tang research groups, who observed the formation of 2-benzoxepines as a result of Cu-catalyzed formal [6+1] cycloaddition of arylidene β-dicarbonyl compounds and diazoacetic or diazomalonic ester , (Scheme , b). Hitherto, the only example of 2-benzoxepine formation from a vinyl diazo compound and indane-1,2,3-trione (path B) was described by Hamaguchi and Tamura (Scheme , c).…”
Section: Introductionmentioning
confidence: 99%
“…12−19 The other reaction probabilities are formations of dioxolane, dihydrofuran, furan, and dioxole derivatives. 15,16,20−27 Extending the conjugation to α, β, γ, δ -positions might allow the synthesis of dihydrobenzoxepines 28,29 and other large ring sizes (Scheme 1). After Spencer's 25−27 pioneering work, several studies on the catalyzed reactions of ene/poly-ene-carbonyls with diazo compounds have been realized.…”
Section: Introductionmentioning
confidence: 99%